GE_GERICHTE P/21879/2019 vom 13. Juli 2021 - GE Cour de justice (2021)
CONTRAVENTION;MANIFESTATION;DOMAINE PUBLIC;PREUVE ILLICITE;VIDÉOSURVEILLANCE;DONNÉES PERSONNELLES | LMDPu.2; CC.664; CPP.9; CPP.141; CPP.260; LIPAD.42